Užsienio literatūros suvestinių katalogų leidimas LTSR - Basiulis, Jonas (Knygotyra, 1985)
The present state and history of the edition of the union catalogue of foreign literature is the main topic of the article. The history of the edition could be divided into three stages: 1956–1961; 1967–1974; 1974 till now. Until 1961 the union catalogue of foreign literature was being edited by the State library of Lit. SSR. There were three series: culture and sport. Agriculture (two volumes have been edited); B – Biology. Medicine. Physical culture and sport. Agriculture (two vol. have been edited); C – Natural sciences. Engineering (three vol. have been edited). The publication of the catalogue was not regular and it was not suitable for current information. After some interruption, in 1967 the edition of the catalogue was resumed by the Central library of Lit. SSR Academy of Sciences. The typographical design, appearance and regularity was changed radically. The union catalogue began to inform regularely three libraries of the Republic about the entire files of foreign literature, which were received in the Republic. In 1974 began the third stage of the edition. The Lithuanian Institute of Scientific Information took the initiative in publishing by electronic computers in collaboration with the Public Library for Science and Engineering of the USSR, the Central Library of the Lit. SSR Academy of Science and the Chaires of librarianship and information science of the Vilnius State University. The article summarizes the positive and negative features of the catalogue, and gives some proposals for improving its quality. There are some doubts about the expedience of the union catalogue only for foreign literature. The proposal is given to include the foreign literature into the lists of branch current literature.